THE UNIQUE PLACE OF THE CONCEPT OF SPEECH CULTURE LINGUISTICS - Nigora Bafoyeva Azimovna; Sayfilloyeva Olima G’anijon qizi (Лучшие интеллектуальные исследования, 2024)
Abstract: In the article, the concept of speech culture is scientifically researched scientific opinions are based on facts.